2010
DOI: 10.1177/0022146510368933
|View full text |Cite
|
Sign up to set email alerts
|

Do Personality Traits Moderate the Effect of Late-Life Spousal Loss on Psychological Distress?

Abstract: We use data from the Changing Lives of Older Couples (CLOC) study to investigate the extent to which: (1) five personality traits (agreeableness, conscientiousness, emotional stability/neuroticism, extraversion, and openness) moderate the effect of late-life spousal loss on depressive symptoms; (2) these patterns vary based on the expectedness of the death; and (3) the patterns documented in (1) and (2) are explained by secondary stressors and social support. Widowed persons report significantly more depressiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
45
1

Year Published

2011
2011
2021
2021

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 56 publications
(49 citation statements)
references
References 48 publications
3
45
1
Order By: Relevance
“…Pai and Carr (2010) reported that C lessens the effect of spousal loss on depressive symptoms among adults. Drawing on daily diary data, O'Connor et al (2009) reported that C did not moderate the effects of daily hassles on health-related behaviors, but several facets of C did have significant effects.…”
Section: Avoidance and Neutralization Of Stressorsmentioning
confidence: 98%
“…Pai and Carr (2010) reported that C lessens the effect of spousal loss on depressive symptoms among adults. Drawing on daily diary data, O'Connor et al (2009) reported that C did not moderate the effects of daily hassles on health-related behaviors, but several facets of C did have significant effects.…”
Section: Avoidance and Neutralization Of Stressorsmentioning
confidence: 98%
“…Given that clinical depression is the exception rather than the norm in the face of late-life spousal loss, researchers seek to identify the psychosocial resources that protect against distress among the recently bereaved. Studies have documented the protective effects of social support (Bisconti, Bergeman, & Boker, 2006), economic resources (van Grootheest, Beekman, Broese van Groenou, & Deeg, 1999), and personal attributes such as personality traits (Pai & Carr, 2010). Researchers also have investigated the extent to which religious beliefs and practices protect against loss-related distress (Becker et al, 2007;Pargament, 1997;Pargament, Smith, Koenig, & Perez, 1998;Sherkat & Reed, 1992).…”
mentioning
confidence: 99%
“…In the present study the NEO-FFI traits of interest were neuroticism and conscientiousness. Using Cronbach´s coefficient alpha, the internal consistency in the present study was for Neuroticism, α= .81 and Conscientiousness, α= .82 which can be compared to Neuroticism, α= .73 and Conscientiousness, α= .73 in the Changing Lives of Older Couples-study (Pai & Carr, 2010).…”
Section: Methodsmentioning
confidence: 68%